Ethical dilemma and thinking of Traditional Chinese Medicine nursing (中医护理的伦理困境与思考) - DENG Yao (邓瑶); XIANG Xiaorun (向小润); ZHANG Sha (张沙); LIU Lei (刘蕾) (中西医结合护理)
With the rapid development of Traditional Chinese Medicine in the field of modern medicine, medical ethics issues have gradually attracted the attention of scholars. There is an urgent need for a better understanding and addressing ethical dilemma of Traditional Chinese Medicine in clinical practice. This paper expounds on the concept of nursing ethical dilemma, the development of nursing ethics at home and abroad, and the research status of nursing ethics of Traditional Chinese Medicine, summarizes the existing ethical dilemma of Traditional Chinese Medicine nursing and makes corresponding thinking, to provide reference for finding a solution to the ethical dilemma of traditional Chinese medicine nursing. (随着中国传统医学在现代医疗领域中迅速发展, 医学伦理问题逐渐引起学者们的重视, 中医护理在实践中遇到的伦理困境是当下需要思考和解决的重要内容。本文通过对护理伦理困境的概念、国内外护理伦理发展及中医护理伦理的研究现状进行阐述, 总结中医护理存在的伦理困境, 并做出相应思考, 以期为寻找中医护理伦理困境的解决方案提供参考。)